144k views
0 votes
How to solve 42j+18-19j=-28

User LauraNMS
by
4.9k points

2 Answers

2 votes

Answer:

j = -2

Explanation:

Simplify. First, combine like terms:

(42j - 19j) + 18 = -28

23j + 18 = -28

Isolate the variable, j. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

PEMDAS is the order of operation, and equals:

Parenthesis

Exponents (& roots)

Multiplication

Division

Addition

Subtraction.

~

First, subtract 18 from both sides:

23j + 18 (-18) = - 28 (-18)

23j = -28 - 18

23j = -46

Isolate the variable, j. Divide 23 from both sides:

(23j)/23 = (-46)/23

j = -46/23

j = -2

j = -2 is your answer.

~

User John Garland
by
5.1k points
3 votes

Answer:

j=-2

Explanation:

42j+18-19j=-28

Combine like terms

23j +18=-28

Subtract 18 from each side

23j +18-18 = -28 -18

23j =-46

Divide each side by 23

23j/23 = -46/23

j = -2

User Barney
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.